Cold Lining and Mist Lining: insights and possibilities of adaptation to the mediterranean climate - Daniele Costantini (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This paper focuses on Cold Lining and its most important development, the Mist Lining technique proposed by J. V. Och. Bibliographic research on Mist Lining adhesives and comparative peeling tests were carried out at the University of Urbino were followed by a conservation treatment, confirming the possibility of adapting the Mist Lining technique to the needs of the Mediterranean climate, substituting the solvents and adhesives used by J.V.Och without any loss of efficiency.